Is warfarin associated with higher risk of thrombus in left atrial appendage than direct oral anticoagulants?. (8th February 2021) - Kagawa, E; Kato, M; Oda, N; Kunita, E; Nagai, M; Shiota, H; Dote, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Thrombus in left atrial appendage (LAA) is associated with cardiogenic ischemic stroke, and anticoagulation therapy is utilized to prevent thromboembolism. Purpose: This study is to investigate the incidence of thrombus in left atrial appendage detected by transoesophageal echocardiography (TOE) under anticoagulation therapy with warfarin or direct oral anticoagulants (DOAC). Methods: Between 2005 and 2016, the patients who underwent TOE under anticoagulation therapy due to atrial fibrillation more than one month were enrolled in this study. The patients were divided into 2 groups according to whether treated with warfarin or DOAC and baseline characteristics and incidence of LAA thrombus were assessed. Results: Among the 313 study patients, 243 (78%) were treated with warfarin. The patients treated with warfarin were elder (median 73 y vs. 67 y [interquartile range 66 – 78 y vs. 58 – 72 y], P < 0.01), the body mass index was lower (23.2 vs. 24.0 [21.0 – 25.4 vs. 21.3 – 26.9], P = 0.03). The prevalence of male sex (64% vs. 71%, P = 0.26) were similar between the 2 groups. The previous history of hypertension (69% vs. 59%, P = 0.10), diabetes (24% vs. 19%, P = 0.32), vascular disease (30% vs. 26%, P = 0.52), and ischemic stroke were similar between the 2 groups (30% vs. 23%, P = 0.22). The prevalence of CHA2DS2-VASc score > 1 (84% vs. 59%, P < 0.01) and the d-dimer level (0.7 vs. 0.5 mcg/ml [0.5 – 1.8 vs. 0.5 – 0.5 mcg/ml], P < 0.01) were higher in the warfarin groups than those of the DOAC. The velocity of LAA was slower in the warfarin group than those of DOAC (35 vs. 55 cm/s [21 – 54 vs. 38 – 68 cm/s], P < 0.01). The incidence of detection of LAA thrombus was 19% in the warfarin group and 3% in the DOAC group (P < 0.01). In the warfarin group, the PT-INR were lower in the patients with LAA thrombus (1.38 vs. 1.66 [1.11 – 1.92 vs. 1.34 – 2.03], P = 0.03). Conclusions: The higher risk of ischemic stroke and out of range PT-INR may be the cause of the higher incidence of LAA thrombus in the patients treated with warfarin than those with DOAC.